Role of Tracheostomy in the Management in Dyspnoea Patients (The Planet, 2025)
Introduction: Tracheostomy is a medical procedure where an opening is created in the neck to place a tube into the trachea to aid in breathing. It is used when patients require prolonged respiratory support or in cases of airway obstruction. The efficacy of tracheostomy for respiratory management depends on several factors, including the underlying condition, timing of the procedure, and patient-specific factors. Objectives: The aim of the study was to evaluate the efficacy of tracheostomy for respiratory management in patients. Methods & Materials: This cross-sectional study was carried out in the Department of Medicine, Mymensingh medical college hospital, Mymensingh, Bangladesh during July 2022 to June 2023. A total of 150 patients were participated in the study. Statistical analyses of the results were be obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences (SPSS-24). Results: In this study, the study population's age distribution, 2(1.33%) children were between the ages of 0-10, whereas 41 (27.33%) people were between the ages of 61 and 70. According to sex distribution, the majority 70% was male and 30% was female. Socioeconomic status of the study population, 45 (30%) of the patients are from the low class and 37 (24.66%) are from the high-class family. Based on duration of hospital stay, it was observed that, 68(45.33%) patients were stays in hospital within 3 days and 43(28.66%) were >3 days. Conclusion: Tracheostomies were more typically performed in young people, with a higher incidence among males. Tracheostomies are typically performed for assisted ventilation in adults and children, with the most common consequences being subcutaneous emphysema and peristomal infections. The majority of the problems were addressed conservatively.
Keywords: Tracheostomy; Respiratory; Airway obstruction; Subcutaneous emphysema; Peristomal infections